2023
DOI: 10.1029/2022ms003303
|View full text |Cite
|
Sign up to set email alerts
|

A Bin and a Bulk Microphysics Scheme Can Be More Alike Than Two Bin Schemes

Abstract: Modeling clouds is hard. As noted in great detail in Morrison, van Lier-Walqui, Fridlind, et al. (2020), the two biggest obstacles are (a) the sheer number of cloud and precipitation particles to predict and (b) the lack of the fundamental understanding of microphysical processes involved. With quintillions of droplets in a typical cloud, it is infeasible to predict the evolution of each droplet and its environment. In addition, there does not exist a fundamental governing equation or benchmark model that can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 40 publications
(74 reference statements)
0
0
0
Order By: Relevance
“…However, the bin schemes should not be treated as “truth” due to numerical broadening (Grabowski et al., 2019; Hill et al., 2023; Morrison et al., 2018) and uncertainty in any scheme about the fundamental physical processes. Such issues result in large differences among bin schemes (Hill et al., 2023; Hu & Igel, 2023a; VanZanten et al., 2011; Xue et al., 2017). We specifically use two reference bin schemes because we recognize that neither is perfect.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the bin schemes should not be treated as “truth” due to numerical broadening (Grabowski et al., 2019; Hill et al., 2023; Morrison et al., 2018) and uncertainty in any scheme about the fundamental physical processes. Such issues result in large differences among bin schemes (Hill et al., 2023; Hu & Igel, 2023a; VanZanten et al., 2011; Xue et al., 2017). We specifically use two reference bin schemes because we recognize that neither is perfect.…”
Section: Methodsmentioning
confidence: 99%
“…The continued struggle of these traditional schemes to accurately simulate warm-phase precipitation (Jing et al, 2017;Kay et al, 2018) has led to a few studies and discussions on the feasibility of a bulk scheme with atypical liquid water treatment (Kogan & Belochitski, 2012;Liu et al, 2023;Szyrmer et al, 2005;van Lier-Walqui et al, 2020). More recently, the idea of a unified liquid water category bulk scheme has been revisited in Igel et al (2022;hereafter I22) and (Hu & Igel, 2023a;hereafter HI23). I22 found that a unified category (1category, 4-moment) bulk scheme was noticeably superior compared to a separate category (2-category, 2moment) bulk scheme when representing collision-coalescence, even though the number of total predicted moments and assumed gamma distributions are the same.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation